2023
DOI: 10.3390/ijms24020934
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omic Factors Associated with Frequency of Upper Respiratory Infections in Developing Infants

Abstract: Susceptibility to upper respiratory infections (URIs) may be influenced by host, microbial, and environmental factors. We hypothesized that multi-omic analyses of molecular factors in infant saliva would identify complex host-environment interactions associated with URI frequency. A cohort study involving 146 infants was used to assess URI frequency in the first year of life. Saliva was collected at 6 months for high-throughput multi-omic measurement of cytokines, microRNAs, transcripts, and microbial RNA. Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Further, miRNAs are stable in saliva and display diagnostic and therapeutic utilities in other pediatric conditions [22][23][24]. Prior studies have demonstrated the potential utility of saliva miRNAs as biomarkers for head and neck cancer, stress and even susceptibility to childhood upper respiratory infections [43][44][45]. These results suggest that saliva miRNA levels may provide unique information about inflammation and the host immune response.…”
Section: Introductionmentioning
confidence: 95%
“…Further, miRNAs are stable in saliva and display diagnostic and therapeutic utilities in other pediatric conditions [22][23][24]. Prior studies have demonstrated the potential utility of saliva miRNAs as biomarkers for head and neck cancer, stress and even susceptibility to childhood upper respiratory infections [43][44][45]. These results suggest that saliva miRNA levels may provide unique information about inflammation and the host immune response.…”
Section: Introductionmentioning
confidence: 95%